Reduced mortality but elevated venous thromboembolism risk following knee and hip arthroplasty in patients with rheumatoid arthritis: A general population-based cohort study - Xinjia Deng; Na Lu; Dongxing Xie; Hui Li; Haochen Wang (PLoS ONE, 2025)
Arthroplasty is indicated for patients with rheumatoid arthritis (RA) who experience significant joint damage, including bone erosions, cartilage degradation and joint deformities. However, studies on its associations with all-cause mortality, cardiovascular disease (CVD), and venous thromboembolism (VTE) among patients with RA are scarce. Our aim was to evaluate the relation of knee arthroplasty or hip arthroplasty to all-cause mortality, relative risk of CVD and incident VTE among patients with RA. We included patients with RA (ages≥20 years) from a large United Kingdom primary care database (i.e., IQVIA Medical Research Database). The primary outcome was all-cause mortality (n = 4,774 for knee arthroplasty, n = 3,362 for hip arthroplasty). The secondary outcomes included incident CVD (n = 4,350 for knee arthroplasty, n = 2,390 for hip arthroplasty) and incident VTE (n = 4,574 for knee arthroplasty, n = 3,174 for hip arthroplasty). We conducted propensity score-matched cohort studies to compare the risks of each outcome between subjects with and without knee arthroplasty (n = 2,387 each) and those with and without hip arthroplasty (n = 1,681 each), respectively. We found that subjects with knee arthroplasty had a 23% lower risk of mortality than those without knee arthroplasty (HR: 0.77, 95%CI: 0.65–0.90). Similarly, a lower, albeit non-statistically significant, risk of mortality was observed among subjects with hip arthroplasty than those without arthroplasty (HR: 0.87, 95%CI: 0.73–1.04). Compared with those without arthroplasty, subjects with knee or hip arthroplasty had a lower risk of CVD. The corresponding HRs were 0.86 (95%CI: 0.73–1.01) and 0.84 (95%CI: 0.69–1.02), respectively. Both subjects with knee or hip arthroplasty showed a higher risk of VTE than their counterparts (HR for knee arthroplasty: 1.63 [95%CI: 1.23–2.17]; HR for hip arthroplasty: 2.19 [95%CI: 1.54–3.11]). The associations of arthroplasty with the risks of mortality, CVD and VTE were generally consistent across strata of age and sex, with HR ranges from 0.71–3.75 for knee arthroplasty and 0.66–3.36 for hip arthroplasty. In this large population-based cohort of patients with RA, knee arthroplasty was associated with a lower risk of all-cause mortality, while both knee and hip arthroplasty were associated with a higher risk of VTE. No significant associations were observed with CVD. These findings highlight potential long-term benefits and risks of joint replacement in RA, but given the observational design and possibility of residual confounding, the results should be interpreted as associations rather than causal effects. Further studies are warranted to confirm these observations and to better understand the mechanisms underlying these associations.